Examining the Empathetic Tendency Levels of the Athletes Dealing with Team and Individual Sports - Selçuk Buğdaycı; Uğur Abakay; Zeliha Abakay (Selcuk University, 2019)
Abstract The aim of this study is to determine the empathetic tendency levels of the athletes dealing with team and individual sports, and to specify whether there is a statistically significant difference concerning gender and sports experience variables. In total, 524 volunteer athletes (232 males and 292 females) participated in the study, whose ages ranged between 15 and 27. The "Empathy in the Sports Environment (ESE)" scale, which was developed by Erkuş and Yakupoğlu (2001), was used in the study for the data collection. The SPSS 22.0 package program was used in the analyses of the data. The Independent Samples T test was employed for the paired comparisons, and the Spearman's rho correlation analysis for determining the relations among the variables. The significance level was accepted as p lt;0.05 in the evaluation of the results. As the conclusion of the study, it was determined that there was statistically no significant difference between the athletes dealing with team and individual sports concerning the emotional empathy dimension; however, it was determined that the athletes dealing with team sports gained higher scores in the prediction dimension; it was found that the emotional empathy scores of the female athletes were higher for the gender variable and male athletes had higher scores concerning the prediction dimension. Considering the sports experience dimension, it was determined that the higher the years of experience, the higher the levels of emotional empathy and prediction.